Flexible substrates enabled highly integrated patterns with submicron precision toward intrinsically stretchable circuits. Issue 3 (31st March 2022) - Lv, Wenkun; Liu, Zhaoxin; Li, Zheng; Han, Zhifei; Yang, Yongrui; Li, Qi; Qiao, Yali; Song, Yanlin
Abstract: Fabricating high integration density, high resolution, and intrinsically stretchable patterns by patterned technologies remain challenging. Template printing enabled high‐precision patterned fabrication at a facile operation. However, the pattern spacing constraint is the major limitation to high integration density. In this study, we develop an elastomer‐assisted strategy to improve the template printing process, which involves patterning on the prestrain elastic substrate. This strategy overcomes the spacing limitation and enables the realization of a centimeter‐scale pattern with submicron precision. Particularly, the integration density of fabricated intrinsically stretchable patterns can reach 1932 lines on a substrate of 0.5 cm 2 ; the assembly lines with a feature size of 880 nm and an interval of 955 nm. Furthermore, we demonstrate a facile approach for constructing silver nanoparticle/liquid metal alloy composite conductive patterns. The as‐prepared flexible electrodes can withstand up to 150% strain and a 2‐mm bend radius. This method provides new insights into template printing technology. Additionally, it opens a route for the simultaneous construction of functional patterned arrays with large scale, high integration density, and intrinsic stretchability, which will be useful for the integrated fabrication of various flexible electronic devices. Abstract : The spacing of patterns is as important as the linewidth precision for high integration devices. We develop an elastomer‐assisted template printing strategy to construct highly integrated patterns with submicron‐precision, centimeter‐scale scalability, and intrinsically high stretchability, revealing great potential in flexible electronics.